Cultural landscape study for Malay middle landscape In Lenggong / Marina Abdullah ... [et al.] - Abdullah, Marina; Shuib, Kamarul Bahrain; Mazehan, Mariamah; Hashim, Habsah (2014)
Place and cultures have been meeting and mixing in Malaysia since the very beginning of its history. Colonization often shaped the minds of the population they settled for generations. However, one area that was left out and less valued in terms of its cultural landscape are the middle landscape. Cultural landscape is a property that represents the “combined works of nature and man”. Thus, conserving the cultural landscape is significant to ensure that it is not taken up by rapid development, climate change and also other threats. Objectives are to identify significance in middle landscape and to recommend ways to improve public understanding in landscape conservation. Visual study and oral information from local community was been carried. Value of a place comes from the perception of community towards the surrounding landscape environments. The expected outcome shall be landscape values as highlighted by the communities and these in turn help to strengthen the landscape conservation strategies.